(untitled) (Sebha University Conference Proceedings, 2024)
Thirty albino Wistar rats were used in this research to investigate the effect of the hypothyroidism-inducing drug propylthiouracil on the pregnancy function and phenotypes of rat offspring, including 10 males for mating only, and 20 females were divided into two groups, namely control and treated, and the stages of the estrous cycle of females were determined by vaginal swab test. The stages of the estrous cycle of females were determined by vaginal smear test, and experimental hypothyroidism was induced with propylthiouracil at a concentration of 10 mg/kg for 30 days by oral cavage. The pregnancy period and number of pups were recorded in both groups and the weights of the pups were taken during a 4-week period using a sensitive scale. The results of this study showed a clear appearance of nucleated and keratinised epithelial cells during the proestrus phase compared to the estrus phase, where a number of large nucleated cells were observed with a high number of keratinised epithelial cells. The phenotypic results of rats showed non-significant differences in the pregnancy period and the number of pups, while the drug achieved negative results on the rats by reducing the weight of the pups in the treatment group 24.93±88 compared to the control.